Respuesta :
Answer:
10x - 3x + 7
=(10x - 3x) + 7
= 7x - 7
=7(x - 1)
Step-by-step explanation:
Answer:
7x+7
Step-by-step explanation:
1. Collect Like Terms By Subtracting Their Coefficients
(10-3)x+7
2. Subtract The Numbers
7x+7
![Ver imagen azocher26](https://us-static.z-dn.net/files/d0f/ae60b0919ab2fffff05739a572a87262.jpg)
Answer:
10x - 3x + 7
=(10x - 3x) + 7
= 7x - 7
=7(x - 1)
Step-by-step explanation:
Answer:
7x+7
Step-by-step explanation:
1. Collect Like Terms By Subtracting Their Coefficients
(10-3)x+7
2. Subtract The Numbers
7x+7